GATA4 variant identified by whole‐exome sequencing in a Japanese family with atrial septal defect: Implications for male sex development. Issue 11 (11th October 2018) - Shimizu, Daisuke; Iwashima, Satoru; Sato, Keisuke; Hayano, Satoshi; Fukami, Maki; Saitsu, Hirotomo; Ogata, Tsutomu
Key Clinical Message: We identified a heterozygous p.(R284H) variant of GATA4 in a Japanese family with atrial septal defect, including boys with apparently normal male sex development. The findings, together with the previous data, imply that GATA4 variants primarily cause congenital heart disease and rarely result in 46, XY disorder of sex development. Abstract : We identified a heterozygous p.(R284H) variant of GATA4 in a Japanese family with atrial septal defect, including boys with apparently normal male sex development. The findings, together with the previous data, imply that GATA4 variants primarily cause congenital heart disease and rarely result in 46, XY disorder of sex development.